The Crown Witness From the Point of View of Islamic Criminal Law in Truth Discovery of Criminal Cases in Indonesia - Zulhendra, Joni; Firdaus, Firdaus; Wirman, Hardi Putra (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This article aims to elucidateÂ  Islamic criminal law's point of view on the existence of crown witnesses in the truth discovery of criminal cases in Indonesia. In fulfilling the shortage of witness evidence, one of the perpetrators of the crime was carried as a case witness in the case. This study uses normative research methods by reviewing books relevant to the problem (Library Research) by tracing, comparing, and analyzing normative doctrinal law through a qualitative approach regarding crown witnesses. This study found that Islamic criminal law requires fairness to be accepted as a witness. If a crown witness is indeed needed as evidence to reveal a criminal case without being accompanied by other supporting evidence, then a crown witness is permitted. Should there is other evidence, the crown witness will be disqualified because the crown witness does not meet fair requirements. The rule of law in Indonesia based on the Criminal Procedure Code (KUHAP) article 185 paragraph 2 states that the statement of one witness is insufficient to prove a criminal case called the principle of unus testis nullus testis (one witness is not a witness). Therefore, there are no other witnesses apart from the crown witness.